Pengaruh Kualitas Pelayanan Praktik Rehabilitasi Bersumberdaya Masyarakat (RBM) Terhadap Kepuasan Orangtua Atau Keluarga Pasien Di Kecamatan Gondangrejo Kabupaten Karanganyar - Roy Romey Daulas M; Sudarman Sudarman (Poltekkes Kemenkes Surakarta, 2018)
Abstract Background: The practice of Community Resource Rehabilitation (RBM) was carried out by Speech Therapy Department students in the area of the target village of the Therapy Department. The speech was from the Surakarta Ministry of Health Polytechnic in the Gondangrejo District. The RBM has a philosophical foundation from, by and for the community which implies that social rehabilitation activities carried out are initiated by the local government and the community where they are parents/ family and Disability itself which is directly carried out from, by and for the community. Based on the above, then along with the paradigm shift has changed the handling and range of services that were initially institutional-based based into community-based services. Method: This type of research is a quantitative study with an analytical observational design through a cross sectional approach (Cross Sectional. The population in this study was all parents/ families of patients in Godangrejo Subdistrict, Karanganyar District who have disability children or special needs who have received rehabilitation services Community Resources (RBM) by Speech Therapy Department students. Results: Univariate test results on variable Quality of service practices of RBM in general, showed that the majority of respondents rated the service quality of RBM practices by students as